Xanthogranulomatous osteomyelitis of femur masquerading as neoplasm - salloum, Alaa (Latakia University Journal -Medical Sciences Series, 2019)
Xanthogranulomatous osteomyelitis (XO) is a very rare chronic granulomatous inflammation. It can mimic malignant bone tumors on its clinical presentation, gross features, and radiological imaging. However, histopathological examination can differentiate it from malignancy. We describe the case of a 12-year-old child presented with fever and pain in the right knee joint for 2 months. Plain radiography and CT scan- imaging of the right knee joint revealed osteolytic lesion in the lower metaphyseal region of femur. With this clinical presentation and radiological imaging, a diagnosis of primary bone tumor was made. However, XO was confirmed by histopathological examination. This case highlights the rare occurrence and also it can mimic as bone tumor. التهاب العظم والنقي الورمي الحبيبي الأصفر Xanthogranulomatous osteomyelitis هو التهاب حبيبي مزمن نادر للغاية , يمكن أن يقلد أورام العظام الخبيثة بأعراضه السريرية والشعاعية, على أية حال التشريح المرضي يمكن أن يميزه عن الخباثة. وصفنا حالة سريرية لطفل بعمر 12 سنة قدم الى قسم الاطفال في مشفى تشرين الجامعي بشكوى حمى مع ألم بالركبة اليمنى بدأ منذ شهرين , التصوير الشعاعي البسيط والطبقي المحوري للركبة والفخذ الأيمن أظهر وجود أفة حالة للعظم في المنطقة الكردوسية للنهاية السفلية للفخذ. تبعا لهذه الأعراض السريرية والعلامات الشعاعية تم تشخيص ورم عظمي. تم تشخيص الحالة كالتهاب عظم ونقي حبيبي أصفر بعد التشريح المرضي. تسلط هذه الحالة الضوء على الحدوث النادر للمرض وعلى امكانية تقليده للاورام.